Natural Products: The Master Regulators of Antiviral Cytokines - Song, Xun; Xiao, Hai-Tao; Liao, Cheng-Hui; Li, Lu; Kang, Qiang-Rong; Jiang, Ying-Chun; Hu, Xiao-Peng; Zheng, Kai; Fan, Long; He, Zhen-Dan (Current Organic Chemistry, 2017)
Background: The human body has natural defenses against viruses. During the virus infection, as a self-protective mechanism, immune cells and other cells will secrete amount of antiviral cytokines to promote the host to clear virus and microorganism, with multiple mechanisms such as alteration of major histocompatibility complex (MHC) molecules, activation of cellular antiviral responses involving natural killer cells (NK cells) and cytotoxic lymphocytes (CTLs), production of antiviral proteins and antibodies. Natural products as traditional pharmaceutical sources for the curability of various illnesses in the form of medicines possess immunostimulatory properties to enhance the immune system and eventually combat the disease or infection. In the past 20 years, numerous natural products have been subjected to investigation for their antiviral effects and many of them such as polyphenols, flavonoids, saponins and polysaccharides exhibit significant antiviral effects via regulation of these cytokines, specifically interferons (IFNs), tumor necrosis factor α (TNF-α) and interleukins (ILs). Objective: The purpose of this review is to provide an overview of antiviral cytokines and regulation functions of natural products on antiviral cytokines, demonstrating natural products as a promising source for discovery of antiviral agents for the prevention and treatment of virus infection via regulating endogenous antiviral cytokines.
Keywords: virus